PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, KEPEMILIKAN SAHAM PUBLIK DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN LAPORAN CORPORATE SOCIAL RESPONSIBILITY : (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021) - Rizka Dwi Firdani; Tati Rosyati (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
The aim of this study is to identify and empirically demonstrate the effect of Good Corporate Governance, public share ownership and firm size on the disclosure of corporate social responsibility. Data collection techniques using secondary data. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2017-2021. The sample selection in this study was purposive sampling method, therefore the final sample consisted of 10 companies with 50 observational data. The method of analysis and hypothesis testing is through panel regression analysis using Eviews-9. Based on data processing, the research results show that Good Corporate Governance is proxied by the Board of Commissioners and the Audit Committee, other variables, namely Public Share Ownership and Company Size, simultaneously affect the Disclosure of Corporate Social Responsibility. The Audit Committee and Company Size partially have significant effect on Corporate Social Responsibility Disclosure. Meanwhile, the Board of Commissioners and Public Share Ownership partially do not have effect on the Disclosure of Corporate Social Responsibility.